3D printing rocks for geo-educational, technical, and hobbyist pursuits - Squelch, Andrew (Oxford University Press, 2017)
© 2017 The Authors. Advancements in 3D printing technologies, availability of online bureaus offering 3D printing services, and affordable high-resolution digital cameras (including those in smartphones) present opportunities for novel ways to visualize and interact with rocks and rock surface data. This paper documents and explores some of these opportunities with examples produced using the full-color binder jetting 3D printing technology. Opportunities include use by geo-educators, geotechnical investigators, museum curators, model railway hobbyists, and others who have a professional or informal interest in rocks and rock outcrops.